Inconsistency of Salafi’s Bid’ah Concept: Shifting The Quran-Hadis Law Consideration During Covid-19 Pandemic in Indonesia - Putra, D.I. Ansusa; Sayuti, Sayuti; Rahim , Rahimin Affandi Abdul (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
For the past century, bid’ah (in English know as religious innovation) has been a fundamental sociological problem in modern Muslim life. Regarding this aspect, during the COVID-19 pandemic, Salafi group in Indonesia used a different method to evaluate bid’ah in the rules of Islamic practices. Therefore, this research aimed to illustrate the dynamics of Salafi understanding of bid’ah in Indonesia during the COVID-19 pandemic. The data collected were acquired digitally from the YouTube platforms of the following Salafi figures Syafiq Riza Basalamah, and Firanda Andirja as well as written documents, uploaded websites, such as rumaysho.com by Muhammad Abduh Tuasikal, almanhaj.or.id by Yazid bin 'Abdul Qadir Jawas, and others. The result showed that Salafi provided new innovations in religious practices during the COVID-19 pandemic. This showed the inconsistency associated with Salafi teachings in bid’ah because it shifted from the Qur’an and Hadith. The inconsistency was carried out by quoting the Qur’an and Hadith from the Ashalah (puritanism) and the maslahah (public interest). This was aimed at selecting legal propositions to the conditions of the thaun (plague). In conclusion, the inconsistency of Salafi by accepting bid’ah (new innovations) to gain Covid-19 survival is proof of the acceptability of Salafi fiqh to social change.